Kinerja Papan Komposit Ramah Lingkungan Terhadap Api: Studi Literatur - Rizky Dwiandra Putra; Dangan Waluyo; Timbul Siahaan; Nurul Ilmi; Alvin Muhammad Savero (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Natural fiber-based composite boards have gained increasing attention as a sustainable and eco-friendly alternative to conventional construction materials. While these materials offer notable mechanical performance and material efficiency, one of the primary challenges lies in improving their resistance to fire. This review presents a comprehensive analysis of existing literature on the fire performance of natural fiber composites, focusing on the role of fiber type, resin formulation, flame retardant additives, and production techniques. Based on a synthesis of ten experimental studies, it was found that composites combining kenaf fibers with phenolic resin and ammonium polyphosphate (APP) demonstrated the highest fire resistance—indicated by a Limiting Oxygen Index (LOI) exceeding 30%, longer ignition times, and slower burn rates. Additionally, fabrication methods such as hot pressing and surface coating proved effective in enhancing thermal resistance. Despite their promise, the adoption of these composites in broader industrial applications is hindered by challenges including energy efficiency, additive costs, and long-term stability. This review suggests that future development should integrate innovative material science with sustainable manufacturing strategies to produce fire-safe, cost-effective, and environmentally responsible composite panels.